2013
DOI: 10.1016/j.powtec.2012.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the milling parameters on the mechanical work intensity in planetary mills

Abstract: The formation of ZnSe via a mechanically-induced self-sustaining reaction (MSR) from a Zn/Se mixture showed that only size reduction and mixing of the reactants without product formation occurred during the induction period prior to ignition. Therefore, all mechanical energy supplied by the planetary mill during this time, called the ignition time (t ig ), was used exclusively in the activation of the reactants. This system was chosen to study the dependence of t ig on the main parameters characterising the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 27 publications
(36 reference statements)
1
50
0
Order By: Relevance
“…First, the ceramic phase, i.e., the Ti-Ta carbonitride solid solution with nominal composition Ti 0.95 Ta 0.05 C 0.5 N 0.5 , was synthesised from the starting materials by the mechanochemical MSR process using a planetary mill (Pulverisette 4, Fritsch) that allowed for operation at a constant gas pressure and for the detection of self-propagating reactions during milling [39]. This composition was chosen according to a previous study that showed that the presence of Ta significantly improves the oxidation resistance of cermets [40], which is of crucial importance for high-temperature applications.…”
Section: Development Of Cermetsmentioning
confidence: 99%
“…First, the ceramic phase, i.e., the Ti-Ta carbonitride solid solution with nominal composition Ti 0.95 Ta 0.05 C 0.5 N 0.5 , was synthesised from the starting materials by the mechanochemical MSR process using a planetary mill (Pulverisette 4, Fritsch) that allowed for operation at a constant gas pressure and for the detection of self-propagating reactions during milling [39]. This composition was chosen according to a previous study that showed that the presence of Ta significantly improves the oxidation resistance of cermets [40], which is of crucial importance for high-temperature applications.…”
Section: Development Of Cermetsmentioning
confidence: 99%
“…The position of this peak shows the ignition time. The system used in this work has already been illustrated elsewhere [22]. Magnesium oxide by-product was removed by leaching the as-milled powder in a CHNS-932).…”
Section: Methodsmentioning
confidence: 99%
“…The position of this peak shows the ignition time. The system used in this work has already been illustrated elsewhere [22]. Magnesium oxide by-product was removed by leaching the as-milled powder in a 1M-HCl solution at 80 °C for 1 h.…”
Section: Methodsmentioning
confidence: 99%